Evaluation of reproductive traits of Chokla sheep under semi-arid conditions of Rajasthan - MEHROTRA, ARNAV; PANNU, URMILA; CHOPRA, ASHISH; NARULA, H K; PATEL, A K (The Indian Journal of Animal Sciences, 2019)
The study analysed the records of 1,172 ewes maintained at ICAR–Central Sheep and Wool Research Institute at Avikanagar and Bikaner, Rajasthan over a period of 22 years (1994-2016). Eight reproductive traits were assessed, namely age at first service (AFS; 572.39±6.59 days), age at first successful service (ASS; 635.71±9.36 days), age at first lambing (AFL; 773±8.77 days), weight at first service (WFS; 25.16±0.11 kg), weight at first successful service (WSS; 25.85±0.16 kg), weight at lambing (WL; 28.61±0.21 kg), lambing interval (LI;371±6.87days) and service period (SP; 228.31±6.62 days). The effects of period of birth of ewe, ewe’s birth weight and sire were significant for all the traits except LI and SP with an improvement of 17.47% –37.6% observed over the period of study. Season of birth of ewe had significant effect on AFL. AFS, ASS and AFL were significantly influenced by their respective covariates (WFS, WSS and WL). The statistically significant improvement over the periods suggest that through suitable selective breeding policy and good managemental measures, the reproductive performance of the flock can be enhanced. The optimization of ewe weights could reduce the age of sexual maturity and the ewe’s weight at birth may serve as an indicator for future performance in this regard. Selection of superior sires may improve the genetic potential of the flock with respect to the reproductive traits.